Ghana : Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This report highlights Ghana's Poverty Reduction Strategy Paper (PRSP). The Ghana Poverty Reduction Strategy (GPRS) represents comprehensive policies, strategies, programs, and projects to support growth and poverty reduction from 2002 to 2004. The GPRS will also focus on providing the enabling environment that will empower all Ghanaians to participate in wealth creation and to partake in the wealth created. The GPRS aims at removing key obstacles to access and use, by the poor, of basic education, health care, population control, good drinking water, and improved sanitation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet